China-made robot-assisted unicompartmental knee arthroplasty can enhance the precision of prosthesis placement and yield better short-term efficacy - Rongxin Sun; Wusiman Yilihamujiang; Abulaiti Aierxiding; Gang Cheng; Zhoujun Zhu; Zhang Lei; Jian Gao; Guangjun Zhong; Maimaitiyiming Mieradili; Yeersheng Releken; Kan Jiang (Journal of Orthopaedic Surgery)
Background The purpose of this study was to assess whether China-made robot-assisted medial UKA can improve prosthesis placement accuracy and yield superior short-term outcomes compared with conventional UKA. Methods 50 patients who underwent initial medial UKA were included in this single-center, prospective, parallel, randomized, controlled trial. Preoperatively, patients were randomly categorized the robot-assisted UKA group and conventional UKA group. The operation time, intraoperative blood loss, postoperative pain scores (VAS scores at 24 h, 72 h, and 3 months post-surgery), KSS scores (clinical and functional scores), and knee range of motion (ROM) were compared between the two groups. The coronal deviation values of the femoral component, tibial component, and knee joint line height change were also compared between the two groups. Results The deviations in tibial component coronal plane alignment, femoral component coronal plane alignment, and joint line height change were significantly smaller in the robot-assisted group compared to those in the conventional group ( p < 0.05). The operation time of the robot-assisted group was longer than that of the conventional group ( p < 0.05). At 24 h and 72 h postoperatively, patients in the robot-assisted group reported lower VAS scores compared to those in the conventional group ( p < 0.05). No significant differences were observed between the two groups regarding intraoperative bloodloss, the VAS scores at 3 months postoperatively, the KSS scores (clinical scores and functional scores) at 3 months postoperatively, and the Knee range of motion at 3 months postoperatively. Conclusions The China-made UKA robot can enhance the precision of prosthesis placement, yielding favorable short-term therapeutic outcomes.